From Borrowing to Shared Narratives: Reassessing Abraham Geiger's Hypothesis in the Light of Late Antique Qur'anic Intertextuality - Moh. Nor Ichwan (RaSAIL Media Group, Semarang, Indonesia, 2025)
This study critically reassesses Abraham Geiger's 19th-century hypothesis, which posited that the Qur'an largely borrows from rabbinic texts, through the lens of contemporary Qur'anic intertextuality and late antique studies. Drawing on Geiger's Judaism and Islam as its primary unit of analysis, alongside the Qur'anic text and early rabbinic literature, the article seeks to reposition his influential but methodologically flawed thesis within modern scholarly frameworks. Employing a historical-hermeneutic and intertextual methodology, the analysis moves beyond Geiger's reductionist